PROBLEMS OF PUBLIC SERVICE OF RUSSIAN OFFICIALS - V. I. Sharin (Вестник университета)
The problem of motivation of public service in the civil service, affecting the efficiency and professional level of personnel, is relevant. The research is aimed at studying the problem of motivation of public service in the Russian civil service. The methodological base includes the concept of bureaucracy by M. Weber, the concept of motivation of public service by J. Perry and L. Wise, as well as the publications of leading Russian and foreign scientists in this field. When analysing the data, the methods of system analysis and General scientific methods were used. Scientists and practitioners give ambiguous estimates of the role of motivation of public service in the structure of motivation of officials. Therefore, the aim of the paper is to answer the question: whether the motivation of public service has a significant impact on the motivation of officials to perform public civil service. The analysis of motivational preferences has showed that the motivation of public service is not perceived by the majority of civil servants as the leading motivation of service. The reasons for the lack of motivation of public service among Russian officials have been examined in the paper. According to the results of the study, measures aimed at increasing the motivation of public service of civil servants have been proposed.